Prognostic Significance of Blood Urea Nitrogen in Acute Ischemic Stroke - You, Shoujiang; Zheng, Danni; Zhong, Chongke; Wang, Xianhui; Tang, Weiting; Sheng, Liqin; Zheng, Cheng; Cao, Yongjun; Liu, Chun-Feng (Circulation Journal, 2018)
Background:Prior studies have shown an association between high blood urea nitrogen (BUN) and an elevated risk of mortality in heart failure patients, but data on the prognostic significance of BUN and other markers of kidney function in acute ischemic stroke (AIS) patients are sparse.Methods and Results:A total of 3,355 AIS patients were enrolled from December 2013 to May 2014, across 22 hospitals. Admission BUN was divided into quartiles (Q1, <4.39 mmol/L; Q2, ≥4.39 and <5.40 mmol/L; Q3, ≥5.40 and <6.70 mmol/L and Q4, ≥6.70 mmol/L) and estimated glomerular filtration rate (eGFR), creatinine (Cr) and BUN/Cr were also categorized. Cox proportional hazard and logistic regression models were used to estimate the effect of BUN, eGFR, Cr and BUN/Cr on all-cause in-hospital mortality and poor outcome on discharge (modified Rankin Scale score ≥3) in AIS patients. During hospitalization, 120 patients (3.6%) died from all causes and 1,287 (38.4%) had poor outcome at discharge. BUN was independently associated with all-cause in-hospital mortality (adjusted HR for Q4 vs. Q1, 3.75; 95% CI: 1.53–9.21; P-trend=0.003) but not poor outcome at discharge (P-trend=0.229). No significant association was found, however, between reduced eGFR, increased Cr and BUN/Cr and all-cause in-hospital mortality and poor outcome at discharge (all P-trend ≥0.169).Conclusions:Increased BUN at admission is a significant prognostic factor associated with in-hospital mortality in AIS patients, but not with poor discharge outcome.